Memorial dedicated to Jonathan Duncan - Ghosh, Ayan (2023)
Born in Scotland, Jonathan Duncan came to India at the age of 16. He began his career in India in 1772, and in 1784, he was one of the charter members of the Asiatic Society founded in Calcutta by William Jones. In 1791, he started the Sanskrit College in Benaras to promote the study of Hindu laws and philosophy. His lifelong interest in cultivating Brahminical knowledge is reflected at his memorial, which has a dhoti-clad bare-chested Brahmin scholar.